Review of thermal conductivity in composites: Mechanisms, parameters and theory. (October 2016) - Burger, N.; Laachachi, A.; Ferriol, M.; Lutz, M.; Toniazzo, V.; Ruch, D.
Abstract: Thermal conductivity has become an important parameter for new technologies, especially in aerospace and aeronautics. The advanced materials used in some electronic applications tend to undergo an increase in temperature when they are used. Increasing the thermal conductivity of a material will help to diffuse heat faster to avoid substantial overheating that could lead to premature degradation of the material. This article reviews theoretical and experimental aspects of thermal conductivity in composites, from thermal energy generation to heat transfers. The fundamental mechanism of thermal conduction, its mathematical aspects, and certain essential parameters to be considered in this study, such as crystallinity, phonon scattering, or filler/matrix interfaces are discussed in detail to examine their impact on thermal conductivity, complementing several reviews in the field.